COVID-19 : Tax Policy and Revenue Administration Implications - Junquera-Varela, Raul Felix; Lucas-Mas, Cristian Oliver (World Bank, Washington, DC, 2021)
This note brings together current thinking among global and regional teams on governance and institutional approaches to dealing with COVID-19. With a focus on tax policy and revenue administrations, it presents governance and institutional reforms that could support revenue administration responses to the pandemic.1 COVID-19 has brought about a new normal in which work practices should change. Shocks usually trigger responses, and a productive response here will be to automate tax and customs services over the medium term and to massively accelerate the use of digital and virtual technologies.